Ultramorphological analysis of the venom glands and their histochemical relationship with the convoluted glands in the primitive social paper wasp Polistes versicolor (Hymenoptera: Vespidae) - Britto, F. B. [UNESP]; Caetano, F. H. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
The venom glands are part of the most important defense weapon in Aculeata: the venom apparatus. The arrangement of these glands can vary among species, but in general they are composed of long secretory tubules connected to a muscular sac-like reservoir. Although the occurrence of these variations has been documented, many studies neglected the existence of a well-developed secretory portion in the lumen of the reservoir named convoluted gland. This study is an ultramorphological analysis of the venom glands and their histochemical relationship with the convoluted glands in the primitive social wasp Polistes versicolor. In this wasp, the venom glands are constituted by two tubular portions that penetrate individually in the venom reservoir, inside of which we can find the convoluted glands. Besides morphological differences in their cells, histochemical analysis of the venom and convoluted glands clearly show differences between them. While the venom glands indicate positive reaction only for proteins, the convoluted glands present positive reaction for proteins, neutral glycoconjugates, and lipids. The secretion of the convoluted gland cells may modify the compounds passing through the embedded tubular region.
Keywords: wasps; venom glands; convoluted glands; ultramorphology; histochemistry